The Social Media Presence of Non-profit Organizations - Lucky, Shannon; Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Social media technologies have the potential to be powerful knowledge sharing and community building tools for both corporate and non-profit interests. This pilot study explores the social media presence of a group of forty-six Alberta-based non-profit organizations (NPOs) in this information rich space. In this paper we look at the pattern of presence of NPOs using social media and relationships with staffing structures. Les médias sociaux ont la capacité d’être de puissants outils de partage de la connaissance et de rassemblement communautaire pour les organisations à but lucratif et sans but lucratif. Cette étude pilote explore la présence dans les médias sociaux d’un groupe de quarante-six organisations sans but lucratif (OSBL) albertaines dans cet environnement riche en information. La communication portera sur les modèles de présence des OSBL dans les médias sociaux et les liens avec les structures organisationnelles.